PENERAPAN MODEL PEMBELAJARAN YANG MAMPU UNTUK MENINGKATKAN HASIL BELAJAR KIMIA DAN KARAKTER KOMUNIKATIF SERTA RASA INGIN TAHU PADA MATERI KIMIA LARUTAN - Titin Rahmayanti Rambe (LPPM STKIP AL MAKSUM, 2019)
The aims of this research is to determine a learning model that can further improve the learning outcomes of chemistry, communicative characters, and the character of students' curiosity on chemistry solutions in high school. The study population was all high school students of class XI IPA in the even semester of the 2013/2014 Academic Year who were taught with curriculum materials in 2013. The samples studied were taken by purposive sampling, namely students of SMA Negeri 1, SMA Negeri 2 and SMA Negeri 7 Medan (respectively as many as three classes and each class consists of 27 students). Each of the three classes was given a treatment in the form of a different learning model. Furthermore, the class that is treated with the direct instruction learning model is called experimental class 1, the class that is treated as a project-based learning model without media is called the experimental class 2, and the class that is treated as a project-based learning model with internet media is called the experimental class 3. collecting student learning outcomes data in the experimental class 1, experimental class 2, and experimental class 3 with the same objective test form, while the instrument used to measure character data from each of the experimental classes is a questionnaire. Data analysis technique used one way ANAVA with SPSS 19 for windows at a significance level α = 0.05. The results showed that: (1) There were significant differences in student chemistry learning outcomes between students who were taught with direct instruction learning models and project-based learning models without media and project-based learning models with internet media on Chemistry Solutions, (2) There were differences curiosity characters of students taught with direct instruction learning models and project-based learning models without media and project-based learning models with internet media, (3) There are differences in the communicative characters of students taught with direct instruction learning models and project-based learning models without media and project-based learning models with internet media, (4) There is a significant relationship between the character of curiosity with the learning outcomes of students taught with the project-based learning model with internet media, (5) There is a significant relationship between communicative characters with student learning outcomes taught by direct instruction learning models, and project-based learning models without media and project-based learning models with internet media, and (6) learning outcomes, curiosity characters, and communicative characters of students taught with learning based models project with the best internet media.